2008
DOI: 10.4028/www.scientific.net/kem.388.57
|View full text |Cite
|
Sign up to set email alerts
|

Shell-Core Type Proton Conducting TiP<sub>2</sub>O<sub>7</sub>-Based Solid Electrolytes

Abstract: Shell-core type TiP2O7-based electrolytes were synthesized by a low-temperature sol-gel method, and their conductivities were investigated by ac-impedance spectroscopy. The samples heat-treated at 500°C showed higher proton conductivities of 3.8 × 10-2 - 1 × 10-2 Scm-1 at intermediate temperatures (100 - 300°C). The conductivity decreased by reheat-treatments at 600°C and 700°C due to a decrease in the amount of the conductive amorphous shells. However, the mechanical strength of the sample pellet significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…[1][2][3][4][5][6] In previous works, 4,7 many authors have reported high ionic conductivity in cerium pyrophosphates in dry atmosphere, however, we have shown that the ionic conductivity of CeP 2 O 7 -based materials in unhumidified air is very low (<10 −7 S cm −1 at <200 • C) but their ionic conductivity increases significantly (more than 5 order of magnitude) on their exposure to moisture. Several approaches have been proposed for the design of phosphate-based anhydrous proton conducting electrolytes in 120-400 • C temperature range.…”
mentioning
confidence: 46%
“…[1][2][3][4][5][6] In previous works, 4,7 many authors have reported high ionic conductivity in cerium pyrophosphates in dry atmosphere, however, we have shown that the ionic conductivity of CeP 2 O 7 -based materials in unhumidified air is very low (<10 −7 S cm −1 at <200 • C) but their ionic conductivity increases significantly (more than 5 order of magnitude) on their exposure to moisture. Several approaches have been proposed for the design of phosphate-based anhydrous proton conducting electrolytes in 120-400 • C temperature range.…”
mentioning
confidence: 46%
“…Onoda et al 19 has reported a value of about 10 −6 S • cm −1 at 400 • C in air with 4.2% H 2 O for the conductivity of Ce(PO 3 ) 4 doped with 1 mol% Gd, but this large difference may be associated with the higher calcination temperature, the higher measuring temperature, lower pH 2 O, and lower degree of doping used by Onoda et al 19 Excess P m O n at the grain boundaries has been suggested by various groups 14,16,[27][28][29] to be the reason behind the high proton conductivities reported for some pyrophosphates, as this could explain the many orders of magnitude difference in conductivity determined for nominally similar compositions. There is consensus as to the fact that the calcination and sintering temperatures can significantly affect the transport properties due to loss of P. 2,3,9,14,15 Two studies that have attempted to vary and quantify the metal to P ratio by X-ray fluorescence (XRF), 2,9 suggested that P deficiency can seriously harm the conductivity, whereas P excess has a small influence. For accurate quantification of the XRF signal though, appropriate calibration standards are necessary in order to account for interactions of the X-rays with the matrix.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies have shown that the transport properties of pyrophosphates are very sensitive to the synthesis method and thermal history of the samples, 2,3,9,14,15 which affect the P content and the phase composition of the investigated powders. Nevertheless, a detailed examination of the phase and composition development with temperature, humidity and over extended time periods is often lacking, which may be the reason behind the large differences in the transport properties reported by different groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations